The association of intensity of joint pain and health-related quality of life among adults with arthritis: a large population-based cross-sectional study - De Moraes-Ferrari, G (BMC, 2025)
BackgroundArthritis imposes serious health consequences, including substantial disability and increased risk of all-cause mortality. Prior studies have reported that pain was associated with decreased health-related quality of life (HRQoL) among individuals with arthritis, yet the association between joint pain severity and HRQoL remains unclear.MethodsThis study analyzed pooled data from 362,366 U.S. adults with arthritis in the 2015-2019 Behavioral Risk Factor Surveillance Survey, categorizing joint pain severity as no/mild (0-3), moderate (4-6), or severe (7-10) via the Numerical Rating Scale. HRQoL was assessed using four domains: self-rated health, physical/mental unhealthy days, and activity limitation. Multivariable logistic regression examined the association between joint pain severity and loss of HRQoL in overall and across demographic subgroups.ResultsCompared to no/mild pain, moderate pain was associated with higher odds of poor self-rated health (OR = 2.18, 95%CI = 2.08-2.27), physical unhealthiness (2.46, 2.35-2.58), mental unhealthiness (2.05, 1.93-2.17), and activity limitation (2.33, 2.20-2.47). Severe pain showed stronger associations (e.g., poor self-rated health: OR = 4.61, 4.40-4.83; physical unhealthiness: 6.74, 6.41-7.09). Subgroup analyses revealed stronger associations in women, Non-Hispanic Whites, and adults aged 45-64 years. Joint pain severity was associated with worse HRQoL, with heterogeneous effects by demographic subgroups.ConclusionsModerate-to-severe joint pain is associated with poorer HRQoL across all domains, with severity-correlated HRQoL decline and subgroup variations. Targeted pain management strategies, particularly for severe pain and vulnerable populations, are critical to improving outcomes in arthritis.